Technical Thermodynamics for Engineers Basics and Applications - Schmidt, Achim; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Thermodynamics is a subject that all engineering students have to face and that most of them treat with great respect. This makes it all the more important to offer a good and easy-to-understand approach to the laws of energy conversion. This is what this textbook is intended to do: It covers the basics of classical technical thermodynamics as they are typically taught at universities: The first and second law of thermodynamics as well as equations of state are explained for idealized and real fluids which are subject to a phase change. Thermodynamic mixtures, e.g. humid air, are treated as well as chemical reactions. Components and thermodynamic cycle that convert energy are presented. The book attaches great importance to drawings and illustrations, which should make it easier to comprehend complex matter. Technical applications and apparatus are presented and explained. Numerous exercises and examples conclude the book and contribute to a better understanding of the theory.
Basics and Ideal Fluids -- Real Fluids and Mixtures -- Reactive Systems.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Fluid mechanics; Engines; Engineering Thermodynamics, Heat and Mass Transfer; Engineering Fluid Dynamics; Engine Technology